(untitled) (Texas Journal of Multidisciplinary Studies, 2023)
As organisation strive to maintain competitive advantage over others, the role of communication cannot be overemphasized. Effective communication plays a crucial role in facilitating the efficient operation of any given institution. This study is driven by two research inquiries, namely: what are the purposes of efficient communication at Kenule Beeson Saro-Wiwa Polytechnic Bori, Rivers State, and what are the barriers to effective communication at Kenule Beeson Saro-Wiwa Polytechnic Bori, Rivers State? The study used primary data collected via questionnaires and secondary data obtained from journals, textbooks, and internet sources. The research style employed was survey research design, and the sampling technique employed was simple random sampling. The main data collected were organised in statistical tables and examined using a four-point Likert rating scale, with criterion mean standard of 2.50. The cybernetics theory served as a conceptual foundation for analysis. The study findings amongst others prove that; communication improves organisational productivity and serves as a channel for generating feedback. Also, the study amongst others recommends that management should train and equip staff with modern communication apparatus and also introduce modern channels of communication at Kenule Beeson SaroWiwa Polytechnic Bori as this will enhance productivity.